2009
DOI: 10.1007/s00421-009-1276-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of heart rate recovery after exercise with indices of obesity in healthy, non-obese adults

Abstract: We aimed at determining whether body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) are associated with heart rate recovery (HRR) and to demonstrate which of the three indices of obesity, is the strongest predictor of HRR in apparently healthy non-obese adults. Three hundred and twenty-five subjects aged 18-66 years participated in the study. Anthropometric indices were measured, and subjects performed cycle ergometer exercise at 75-85% maximum heart rate. Heart rate (HR) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 35 publications
5
20
2
2
Order By: Relevance
“…Similar to our study, another study found that the peak HR, CI and HRR are attenuated in obese individuals compared to those with normal weight [11], but are higher with increasing METS [10,28]. These findings suggest that obesity is associated with autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to our study, another study found that the peak HR, CI and HRR are attenuated in obese individuals compared to those with normal weight [11], but are higher with increasing METS [10,28]. These findings suggest that obesity is associated with autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 80%
“…Obesity has also been implicated in all-cause and CVD-related mortality, accounting for as many as 112,000 excess deaths yearly [7]. Obesity is associated with poor exercise HR profiles, including lower peak HR, slower HRR and lower CI [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…A associação entre obesidade e redução da RFC após esforço pode ser explicada com base em outras pesquisas, as quais constituem evidências diretas ou indiretas dessa relação. Estudos transversais e prospectivos têm demonstrado associação entre RFC atenuada e parâme-tros antropométricos de obesidade, tanto na presença de fatores de risco cardiovasculares 19,20 como na ausência destes 21,22 .…”
Section: Discussionunclassified
“…For non-parametric variables (disease, medications, chronotropic incompetence, and chrono-tropic index), a Chi square for proportions was used and Cramer's V test of association was applied. First, the multiple linear regression utilized the forward step elimination method for independent variables in the model (percent body fat, BMI, MET, WC, WHR, hypertension, diabetes, and age], according to recommendations from literature 13,12,22 .The continuous dependent variable (1 minute HR recovery) was chosen based on previous research 22 . It is noteworthy that the time constant of an earlier phase of the heart rate (e.g.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, a study in obese subjects with low levels of physical fitness revealed an impaired chronotropic index and HRR during and after exercise stress testing 10 . Several studies have shown that parameters of obesity negatively affect HRR following exercise [11][12][13] . Barbosa et al 13 analysed the relationship between body mass index (BMI) and HRR after one minute of exercise and demonstrated that obese subjects (>30 kg/m 2 ) presented higher basal HR and lower maximum HR accompanied by reduced chronotropic reserve.…”
Section: Introductionmentioning
confidence: 99%